Integration of financial and non-financial reports under management conditions - Prodanciuk Mihail (Economy and Sociology, 2013)
The paper presents the assessment of the development of integrated reports overseas and describes the stages of establishment of such a system. The form and structure of corporate reporting is developed, and is differentiated, reflecting the integrated information regarding aspects of financial and non-financial activity: statistical indicators, economical, financial and social, company strategy, future cash flows, the value of human capital, and the stability of the business model. Goals and objectives of corporate reports are determined, which consist in providing reliable information on all company activities in accordance with strategic objectives and management models.The structure of the integrated report takes into consideration the requirements of the management system, of the legislative bodies and other institutions, and is considered the basis for the development of branch reports models. Its structure will depend on the size of the legal-organizational form and the social value of the company in society. The author of the article suggests three approaches to achieving corporate reports in the section of social responsibility indicators; where each company chooses the form of reporting in accordance with the available categories that depend on the size and strategic policy. The suggested integrated reports are instrumental to the observance of the stable development doctrines and will become a tool that, in the near future, will ensure the company an effective interaction with financial markets and the stakeholders of market relations.